Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Kolase Dengan Bahan Bekas Pada Anak Kelompok B TK BA Aisyiyah Blanceran Klaten Tahun Ajaran 2014/2015 - Cahyaningrum, Winda Ayu, Drs. Ilham Sunaryo, M.Pd AUD, Junita Dwi Wardhani, SE. M,Ed (2015)
This research aims to improve fine motor ability of children through activities with collage materials used in children's group B TK BA Blanceran Karanganom Subdistrict Aisyiyah Klaten Regency school year 2014/2015. This type of research this is a class action research (PTK). The subject of action research is the Group B TK BA Aisyiyah Blanceran totalling 15 children. This is a collaborative research between researchers, classroom teacher, and school principal. Data collection using observation, documentation of the work of the son, and the notes field. Class action research was conducted through two cycle 2 meetings. The procedures in this study there are four stages of planning, implementation, observation, and reflection. Data analyzed by comparative technique/ ratio wich compares the results achieved with performance indicators. The results showed that the occurrence of increased fine motor ability of children through activities with collage materials on every cycle. Fine motor ability of children increased from pre to cycle 51,25% to 64,58% in cycle I. On cycle II ability increased to 83,54%. Conclusion of this research is through activities with collage materials can improve the child's fine motor skills.